The influence of yeast on chemical composition and sensory properties of dry white wines. (1st July 2018) - Puertas, B.; Jimenez-Hierro, M.J.; Cantos-Villar, E.; Marrufo-Curtido, A.; Carbú, M.; Cuevas, F.J.; Moreno-Rojas, J.M.; González-Rodríguez, V.E.; Cantoral, J.M.; Ruiz-Moreno, M.J.
Highlights: Fermentative strategy and varietal factors modulated the chemical profile of wines. The chemometric approach identified potential markers for each fermentative strategy. EBBAs and cinnamates highlighted as markers of sequential fermentations. 2-Phenyl acetate and stone fruit highlighted as markers of spontaneous fermentations. The fermentative strategies contributed to variability and quality of white wines. Abstract: This study evaluates the impact on two varietal white wines from 'Chardonnay' and 'Verdejo' cultivars of different fermentative strategies: inoculation with Saccharomyces cerevisiae yeast (CT), sequential inoculation ( Torulaspora delbrueckii / Saccharomyces cerevisiae) (SI), and spontaneous fermentation (SP). The wines' chemical composition was characterized by oenological parameters, organic acids, metals, major volatile compounds, ester compounds and sensory analyses. The fermentative strategy (CT, SI and SP) was found to be a key factor for assessing different styles of white wines. SI wines showed enhanced 'mature fruit' nuances and a chemical profile characterized by higher content of ethyl propanoate, ethyl isobutyrate and ethyl dihydrocinnamate. Meanwhile, the SP wines presented enhanced "stone fruit" nuances possible related to the higher contents of 2-phenyl acetate and isobutyl acetate. After a chemometric approach the above esters were identified as the markers of each fermentative strategy, independently of the variety.